Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Dengan Menggunakan Metode MABAC - Toni Aman Waruwu (Graha Mitra Edukasi, 2023)
1001 Mart is a minimarket which is engaged in selling basic daily needs such as rice, sugar, cooking oil, milk, baby diapers and others. The leadership of 1001 Mart always holds the best employee selection every year, the selection of the best employees is done to increase motivation or morale for employees to work even harder. The problem that occurs in this case is that it is difficult for 1001 Mart to make decisions in selecting the best employees. In this research, to solve the problems experienced by the 1001 Mart, the author designed a decision support system for selecting the best employees at 1001 Mart using the MABAC method. The design of this application uses the php programming language and the MySQL database as data storage media into the system. This decision support system will later assist 1001 Mart in determining the best employees based on predetermined criteria. The MABAC method is also expected to give accurate decision results so that no more mistakes will occur in selecting the best employees at 1001 Mart.